Knowledge, attitudes, and practices of oil and salt intake and related influencing factors in Southwestern China - Zhang, Laixi; Xu, Qi; Jiang, Ke; Li, Zhourong; Wen, Yaqi; Hu, Zhichuan; Xie, Changxiao; Shi, Zumin; Sharma, Manoj; Zhao, Yong (Frontiers in Nutrition, 2024)
Objects Excessive oil and salt consumption is a public health issue, notably in China where intakes surpass WHO guidelines. The present study aims to examine the knowledge, attitudes, and practices of Southwestern China residents regarding oil and salt and explore the influencing factors. Methods This study used convenience sampling to collect data from 7,367 participants aged 18–75 in the Sichuan, Chongqing, Yunnan, and Guizhou regions of China via on-site face-to-face surveys. Descriptive statistics and generalized linear models were used to analyses knowledge, attitudes, and practices about oil and salt intake and their influencing factors among residents of Southwestern China. Results In Southwestern China, residents of Guizhou Province exhibited poor KAP regarding oil and salt. There were urban–rural differences in Yunnan, Sichuan, and Chongqing, and residents living in towns and cities were the favored factors for KAP scores. Groups engaged in self-employment/sales and freelance were risk factors for KAP score. Individuals with higher education was a favorable factor for KAP score. In Yunnan, Sichuan, and Chongqing groups with preference of salty tastes were favorable factors in KAP score. Diabetic patients were more likely to score low on oil and salt-related KAP performance. Conclusion In Southwestern China, residents of Guizhou Province displayed poor results in their KAP regarding oil and salt. The region of the province, ethnicity, urban and rural residence, education, taste preference, and prevalence of chronic diseases were the influencing factors of oil and salt-related KAP scores.